1983
DOI: 10.1897/1552-8618(1983)2[411:heotlb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hexachlorobenzene-Induced Effects on the Lymphocyte Blastogenic Response to Concanavalin a in the Mink and European Ferret

Abstract: Hexachlorobenzene (HCB) was found to depress the lymphocyte blastogenic response of mink (Mustela vison) and European ferrets (Mustela putorius furo) to the plant lectin Concanavalin A (Con-A). A significant reduction in the incorporation of [3H]thymidine was seen in the lymphocytes from adult animals consuming 25 ppm dietary HCB for 8 months. This effect was observed in animals showing no physical signs of distress or toxicity.The in utero and early postnatal exposure of young mink to HCB also resulted in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Decrease in the lymphocyte proliferation by mitogen Con-A (14.23% Table-2 ) is an indication of suppression of T-cell blastogenesis, which is essential for mounting of both the cell-mediated and humoral immune response. Earlier, workers have also reported [ 28 ] reduced lymphocyte blastogenesis response in minks and ferrets exposed to hexachlorobenzene. Depression in cell-mediated immune response in pesticide fed birds, as observed in this study, has also been reported in broilers as measured by lymphocytes migration inhibition test [ 29 ] and lymphocyte stimulation test (LST) using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide dye method [ 25 , 27 , 30 ].…”
Section: Resultsmentioning
confidence: 92%
“…Decrease in the lymphocyte proliferation by mitogen Con-A (14.23% Table-2 ) is an indication of suppression of T-cell blastogenesis, which is essential for mounting of both the cell-mediated and humoral immune response. Earlier, workers have also reported [ 28 ] reduced lymphocyte blastogenesis response in minks and ferrets exposed to hexachlorobenzene. Depression in cell-mediated immune response in pesticide fed birds, as observed in this study, has also been reported in broilers as measured by lymphocytes migration inhibition test [ 29 ] and lymphocyte stimulation test (LST) using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide dye method [ 25 , 27 , 30 ].…”
Section: Resultsmentioning
confidence: 92%
“…Decrease in the lymphocyte proliferation by mitogen Con-A (17.88% Table-2 ) is an indication of suppression of T-cell blastogenesis, which is essential for mounting of both the cell-mediated and humoral immune response. Earlier, workers have also reported the [ 30 ] reduced lymphocyte blastogenesis response in minks and ferrets exposed to hexachlorobenzene. Depression in cell-mediated immune response in pesticide offered birds, as observed in this study has also been reported in broilers as measured by lymphocytes migration inhibition test [ 31 ] and lymphocyte stimulation test (LST) using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide dye method [ 27 , 29 , 32 ].…”
Section: Resultsmentioning
confidence: 97%
“…Bush et al [ 9 ] also demonstrated that darker fur colour occurred in male kits but not female kits with supplemental copper at the 200 mg/kg level. One of the clinical signs of Cu deficiency in mink is hypochromotrichia and some mink farmers have reported feeding supplemental dietary Cu to intensify fur colour in dark mink [ 20 ].…”
Section: Discussionmentioning
confidence: 99%